Media and Communication Studies in Europe: Facing old and new Challenges - Sousa, Helena (2017)
[Excerto] So, what are the biggest challenges of the media and communication field in Europe today? It is obviously very difficult to generalize as Europe integrates different traditions and realities, and Europe itself faces a number of crises at the moment. But I will try to address five overarching challenges and concerns [...]